The influence of partnership quality and breastfeeding on postpartum female sexual function - Matthies, Lina; Wallwiener, Markus; Sohn, Christof; Wallwiener, Stephanie (Archives of gynecology and obstetrics, 2019)
IntroductionFemale sexual dysfunction is known to have a huge impact on quality of life and is highly prevalent during the peripartum period. Several influencing variables were found to be associated with impaired sexual function postpartum, among them breastfeeding and partnership quality. However, little is known about the predictive value of these variables. Therefore, this longitudinal cohort study aimed to examine prospectively the influence of the two variables on sexual function 4-month postpartum.Materials and methodsQuestionnaires were administered to 330 women prenatally (TI, third trimester) and postpartum (TII, 1 week; TIII, 4 months). Medical data were collected from the respondents’ hospital records. The Female Sexual Function Index (FSFI) was used to determine overall sexual function, desire, arousal, lubrication, orgasm, satisfaction, and pain perinatally.ResultsAt all timepoints, mean FSFI scores were below the critical FSFI-score of 26.55. Partnership quality, breastfeeding, high maternal education, and maternal depressive symptoms correlated significantly with FSFI scores postpartum. Further analyses confirmed antenatal partnership quality and breastfeeding behavior as strong predictors of sexual function 4-month postpartum, explaining 24.3% of variance. Women who stopped breastfeeding or never breastfed at all showed the highest FSFI scores.ConclusionOur findings indicate that exclusively breastfeeding women and those who report low partnership quality have an increased likelihood of sexual functioning problems 4-month postpartum. Health-care providers need to be encouraged to counsel on postpartum sexuality and influencing factors during prenatal classes to de-pathologize those changes and to foster a positive approach to peripartum sexuality.
Published online: 16 October 2018
Gesehen am 25.07.2019